2017
DOI: 10.1007/s10549-017-4391-5
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk prediction: an update to the Rosner–Colditz breast cancer incidence model

Abstract: Purpose To update and expand the Rosner-Colditz breast cancer incidence model by evaluating the contributions of more recently identified risk factors as well as predicted percent mammographic density (MD) to breast cancer risk. Methods Using data from the Nurses’ Health Study (NHS) and NHSII, we added adolescent somatotype (9 unit scale), vegetable intake (servings/day), breastfeeding (months), physical activity (MET-hrs/week), and predicted percent MD to the Rosner-Colditz model to determine whether these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Recently, we updated the Rosner–Colditz model by further including early life somatotype [18,31,32]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we updated the Rosner–Colditz model by further including early life somatotype [18,31,32]. …”
Section: Methodsmentioning
confidence: 99%
“…Multiple common genetic risk variants [ 8 ] and breast density [ 9 ], as measured on a mammogram, are additional well-confirmed breast cancer risk factors. Recent studies, though limited, have shown that including genetic risk variants (either individually or as a polygenic risk score [PRS]) and/or mammographic density (MD) significantly improves both the Gail model [ 10 17 ] and the Rosner–Colditz model [ 18 ]. In addition, considerable evidence supports an association of circulating estrogens, androgens, and prolactin with postmenopausal breast cancer risk [ 19 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the well-validated Rosner–Colditz model includes age at menarche, age at first birth, age at subsequent births, age at menopause, family history of BC, body mass index (BMI), alcohol intake, and postmenopausal hormone therapy use ( 14 ). Recent studies demonstrated that the including of genetic risk variants, mammographic density, and endogenous hormones improves the Rosner–Colditz model to predict BC risk ( 11 , 12 ).…”
mentioning
confidence: 99%
“…In the BCSC cohort used to fit their model [61] this pattern was not observed for proliferative disease, and for non-proliferative disease the direction was even reversed (a larger effect for women older than 50y). In the Rosner-Colditz model there is a positive interaction with age at menarche and a negative interaction for the other terms (albeit none are univariately significant in the most recent model at a 5% level [51]), suggesting an older age at menarche is not protective for women with benign disease. These three models have been fitted in populations with individual-level data.…”
Section: Regression Function Modelsmentioning
confidence: 90%